1977
DOI: 10.1289/ehp.7721149
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aliphatic alcohols on the hepatic response to halogenated olefins.

Abstract: The role of alcohols in potentiating the toxicity of halogenated hydrocarbon solvents has been reviewed. The toxicity of carbon tetrachloride and chloroform can be markedly potentiated by prior treatment with ethanol or phenobarbital. Trichloroethylene toxicity may also be potentiated by ethanol ingestion. Prior ethanol ingestion acts by altering biochemical parameters that result in an increased response to subsequent solvent exposure. Simultaneous exposure to both ethanol and trichloroethylene allows for com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The consumption of ethanol prior, or during exposure, to carbon tetrachloride vapors may result in increased toxic effects of carbon tetrachloride [Cornish and Adefuin, 1966;Cornish et al, 1977;Maling et al, 1975;Strubelt et al, 1978;Traiger and Plaa, 19721. There are numerous cases of poisoning and deaths from this combination of exposures [Polacsek et al, 19761.…”
Section: Halogenated Hydrocarbonsmentioning
confidence: 99%
“…The consumption of ethanol prior, or during exposure, to carbon tetrachloride vapors may result in increased toxic effects of carbon tetrachloride [Cornish and Adefuin, 1966;Cornish et al, 1977;Maling et al, 1975;Strubelt et al, 1978;Traiger and Plaa, 19721. There are numerous cases of poisoning and deaths from this combination of exposures [Polacsek et al, 19761.…”
Section: Halogenated Hydrocarbonsmentioning
confidence: 99%
“…Interactions between different solvents and between solv,ents and drugs or ethanol are very insufficiently known but are probably of great importance, since simultaneous exposure to several of these compounds is very common. It is, eg, known that aliphatic alcohols, among others, ethanol, may influence the metabolism of trichloroethylene and potentiate the hepatotoxic eff.ect of chloroform and carbon tetrachloride (22). Recently it has also been shown that simultaneous exposure of rats to ethanol and vinyl chloride leads to a greater number of tumors than the administration of vinyl chloride only (81).…”
Section: High Priority Areas For Future Researchmentioning
confidence: 99%
“…Certain chemicals, for instance alcohols, may potentiate the toxicity of TCE (Muller el (11. 1975;Cornish et al 1977;White & Carlson I98lb). In the present study, the effects from peroral administration of a series of I36 INGA JAKOBSON ET AI,.…”
mentioning
confidence: 99%